2016
DOI: 10.3390/jdb4040029
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Suppressor of Fused in Mid-Corticogenesis Leads to the Expansion of Intermediate Progenitors

Abstract: Neural progenitors in the embryonic neocortex must be tightly regulated in order to generate the correct number and projection neuron subtypes necessary for the formation of functional neocortical circuits. In this study, we show that the intracellular protein Suppressor of Fused (Sufu) regulates the proliferation of intermediate progenitor (IP) cells at later stages of corticogenesis to affect the number of Cux1+ upper layer neurons in the postnatal neocortex. This correlates with abnormal levels of the repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Downstream of Shh receptors, Sufu and Gli have been shown to affect progenitor proliferation. Deletion of Sufu at E13.5 result in ectopic activation of Shh activity leading to an increase in the proliferation of IPs in the SVZ, and consequently, an increase in upper layer 4 PNs [50]. Similarly, reduction or complete removal of Gli3R accelerate the cell cycle [51] and ultimately lead to the failure of RG progenitors to self-renew [32].…”
Section: Mitogenic Roles Of Shh Signaling In Cortical Progenitorsmentioning
confidence: 99%
“…Downstream of Shh receptors, Sufu and Gli have been shown to affect progenitor proliferation. Deletion of Sufu at E13.5 result in ectopic activation of Shh activity leading to an increase in the proliferation of IPs in the SVZ, and consequently, an increase in upper layer 4 PNs [50]. Similarly, reduction or complete removal of Gli3R accelerate the cell cycle [51] and ultimately lead to the failure of RG progenitors to self-renew [32].…”
Section: Mitogenic Roles Of Shh Signaling In Cortical Progenitorsmentioning
confidence: 99%
“…The lack of any significant changes in OB interneurons prompted us to further examine the fate of NSCs and TACs in the dorsal V-SVZ of hGFAP cre/+ ;Sufu fl/fl mice. We previously observed similar expansion of specific cortical progenitors in the embyronic neocortex of conditional Sufu knockouts and found that many were unable to survive (Yabut et al , 2016). Therefore, we investigated whether cells in the dorsal V-SVZ of the neonatal hGFAP cre/+ ;Sufu fl/fl mice were similarly unstable and became apoptotic.…”
Section: Resultsmentioning
confidence: 71%
“…Tbr2+ neural progenitors that typically originate from the embryonic cortical progenitors were significantly reduced whereas Gsx2+ neural progenitors that originate from the embryonic ganglionic eminence (Stenman, Toresson and Campbell, 2003; Brill et al , 2009) were significantly increased. We previously reported that loss of Sufu results in the increase in proliferation of cortical progenitors (resulting in an increase in superficial layer projection neurons in the neocortex) and oligodendrogenesis in the E16.5 neocortex of hGFAP-Cre;Sufu-fl mice (Yabut et al , 2016; Winkler et al , 2018). Thus, two possibilities could explain the reduction in Tbr2+ progenitors: 1) cortical progenitors that generate V-SVZ NSCs were re-specified towards the gliogenic lineage, and/or 2) exhaustion of the cortical RG pool has occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Later in corticogenesis, however, Shh signaling increases in the dorsal forebrain and is required for initiation of oligodendrogenesis. This is accomplished partly by decreased expression of Sufu (Yabut et al, 2015;Yabut et al, 2016), as well as increased Shh ligand brought in by interneurons migrating from the ventral forebrain (Winkler et al, 2018). In this way, tight control over the levels and timing of Shh signals confers both spatial patterning early in development and the later switch from neurogenesis to oligodendrogenesis.…”
Section: Multiple Temporal Roles For Shh Signaling In Cell Fate Specimentioning
confidence: 99%
“…Interestingly, recent studies together with our data presented here suggest that the molecular mechanisms involved in these dual roles might be very similar. Genetic ablation of the Shh repressor, Sufu, in the early dorsal forebrain leads to overactivation of Shh-mediated transcription, resulting in patterning defects in dorsal progenitors (Yabut et al, 2015;Yabut et al, 2016;Yabut et al, 2020). The mis-specified dorsal progenitors ectopically express ventral identity genes, including Gsx1/2, Dlx1/2, Olig2 and Ascl1, and downregulate dorsal identity genes like Emx1/2 and Pax6 (Yabut et al, 2015;Yabut et al, 2020).…”
Section: Multiple Temporal Roles For Shh Signaling In Cell Fate Specimentioning
confidence: 99%